Analisis Pendapatan Usahatani Padi Sawah Di Desa Popontolen Kecamatan Tumpaan Kabupaten Minahasa Selatan - Smith, Jovanka Monalisa Angelina; Laoh, Esry Olly Harryani; Tarore, Melissa Lady Gisela (Sam Ratulangi University, 2024)
The purpose of the study was to determine the amount of rice farming income in Popontolen Village, Tumpaan District, South Minahasa Regency. This research was conducted from May to December 2022. This research was conducted in Popontolen Village, Tumpaan District, South Minahasa Regency. The research used primary data obtained directly from the field through interviews using a questionnaire (list of questions) with respondents (rice farmers). Secondary data obtained from government agencies such as government agencies in the research location, Central Bureau of Statistics, Department of Agriculture and other related parties. Sampling method using simple random sampling method. Data were analyzed descriptively. The results showed that the total cost of production components of rice farming in Popontolen Village, Tumpaan Subdistrict was IDR11,104,666 per planting season. Net income on rice farming per Ha in Popontolen Village, Tumpaan Subdistrict per one planting season is IDR21,437,349. The amount of income received by farmers depends on the land area owned by farmers and the feasibility of rice farming in Popontolen Village, Tumpaan Subdistrict is feasible or profitable. This can be seen from the results of the R / C analysis which is 2.92 which means more than 1.